2020
DOI: 10.1186/s43067-020-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic economic dispatch using hybrid metaheuristics

Abstract: Dynamic economic dispatch problem or DED is an extension of static economic dispatch problem or SED which is used to determine the generation schedule of the committed units so as to meet the predicted load demand over a time horizon at minimum operating cost under ramp rate constraints and other constraints. This work presents an efficient hybrid method based on particle swarm optimization (PSO) and termite colony optimization (TCO) for solving DED problem. The hybrid method employs PSO for global search and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Distributed scheduling is used for optimization in [27]. Heuristic and metaheuristic based optimization is used in [28], [29]. A filter- based weighted average price forecast and a combination of tilting block rates with real-time pricing are discussed [30].…”
Section: Various Approaches In Dsm Techniquesmentioning
confidence: 99%
“…Distributed scheduling is used for optimization in [27]. Heuristic and metaheuristic based optimization is used in [28], [29]. A filter- based weighted average price forecast and a combination of tilting block rates with real-time pricing are discussed [30].…”
Section: Various Approaches In Dsm Techniquesmentioning
confidence: 99%
“…It was observed that CTO performs better than other metaheuristics such as TLBO, DE, GA, PSO etc. Dynamic ELD was solved by hybrid PSO TCO [28]. The hybridization of PSO and TCO favoured faster convergence and produced better quality of solutions.…”
Section: Related Workmentioning
confidence: 99%
“…VOLUME 4, 2016 ELD, ELD with valve point effect, CEED CTO [28] Dynamic ELD PSO TCO [29] ELD considering renewable sources Modified BA [30] ELD with losses QBA [31] Dynamic ELD considering renewable sources PSO [32] ELD with valve point effect QBA [33] ELD with losses PSO [34] Non convex ELD ACS [35] CEED Hybrid FA BA [74] ELD Jaya Algorithm [36] ELD with valve point effect, CEED MBA [37] ELD with valve point effect, ramp rates and prohibited zones Improved PSO [38] Convex and non-convex ELD SHO [39] ELD with ramp rates and prohibited zones WOA [40] Convex, non-convex and dynamic ELD MFO [41] ELD with valve point effect Hybrid GWO [42] ELD with losses Improved PSO [43] ELD with losses AEFA [44] Non-convex ELD ALO [45] ELD with losses ACSS [46] ELD with losses Adaptive PSO [47] ELD with losses Enhanced PSO [48] ELD with losses GWO [49] ELD with losses Enhanced BA [50] CEED QBA [51] Dynamic ELD, CEED Modified ABC [52] CEED Enhanced Cultural algorithm [53] Dynamic CEED Chaotic FA [54] Dynamic CEED TLBO [55] Smooth and non-smooth ELD WCA [56] ELD with renewable resources Hybrid BA [57] Multi-area ELD SSA [75] Multi-area ELD Hybrid Jaya TLBO [58] Multi-area ELD ISFS [76] CEED with renewable sources MOEA/D [59] Multi-area ELD MFO [60] CEED Improved TLBO [61] ELD with losses Modified GWO [62] Dynamic ELD GA PSO…”
Section: Economic Load Dispatch Problemmentioning
confidence: 99%
“…A new modified artificial bee colony algorithm (Secui, 2015b), particle swarm optimization and genetic algorithm techniques (Hussain et al, 2019), chaotic improved harmony search algorithm Several optimization strategies and procedures have been utilized to solve the dynamic economic dispatch (DED) problem with complex objective functions or constraints since the topic was proposed in the 1980s (Rezaie et al, 2019). Literature survey shows to solve this problem using conventional algorithms (Kamli and Amraee, 2017), Dynamic economic dispatch using hybrid meta heuristics (Santra et al, 2020) and Simulated Annealing method (Bouddou et al, 2020) for non-smooth or non-convex cost functions, the majority of these strategies are ineffective. To solve the DED problem, a variety of heuristic optimization methods have been used, including Ant based optimization (Secui, 2015a;Vennila and Rajesh, 2022), Dragon fly based optimization (Chandrasekaran et al, 2021), Hybrid HB-SA algorithm (Vennila et al, 2013), differential evolution techniques (Li et al, 2022;Zou and Gong, 2022), harmony search algorithm (Rezaie et al, 2019), and bee swarm based optimization algorithm (Hussain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%